CREATION AND POSSIBILITIES OF USING THE DATABASE «EPIDEMIOLOGY AND EPIZOOTOLOGU OF PLAGUE IN THE SARI-DZHAS NATURAL ORIGIN AREA OF KYRGYZSTAN» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In the paper is described new database created for estimating and forecasting ofepidemiological and epizootological state in natural origin areas, for example for the Sari-Dzhassub-region of plague circulation, which is located in the Issyk-Kul region of Kyrgyzstan. Thedatabase can be used for different inter-disciplinary research.
Keywords: кара тумоо, инфекциянын табигый аянты, эпидемиология, оорунун пайда болуусу, маалымат базасы.